Development and Application of a Method for Pollution Level Analysis of 16 Phthalate Plasticizers in Pre-prepared Dishes - ZENG Tao, YANG Rong, LI Xiaojing, GAN Pingsheng, LIU Miao, LU Zhuliangzi, LI Yan, BAI Zhijun (Shipin Kexue)
An efficient and rapid gas chromatography-tandem mass spectrometry (GC-MS/MS) method for the simultaneous determination of 16 phthalate plasticizers was established and applied to analyze the contamination levels of these phthalates in commercially available pre-prepared dishes. The results showed that a good linearity (R2 > 0.998) was obtained for all analytes in the concentration range of 0.02–2.00 mg/L, and the limit of detection (LOD) of the method ranged from 0.22 to 5.40 μg/kg. Recoveries at three spiked levels ranged from 79.6% to 117.2% with relative standard deviation (RSD) between 0.6% and 3.7%. In 100 samples, the detection rates of dimethyl phthalate (DMP), dibutyl phthalate (DBP) and bis(2-ethylhexyl) phthalate (DEHP) were 83.0%, 91.0% and 94.0% at concentrations of up to 334.7, 1 960.8 and 1 603.3 μg/kg, respectively. Among these samples, two were found to exceed the standard limits for DBP and DEHP, respectively. The proposed method was characterized by simple pretreatment, low blank control, good recovery, rapid analysis speed and high accuracy. This study provides methodological and data support for food safety risk assessment and supervision in the pre-prepared dish industry.